Using Regression and Correlation Approach to Assess Information Search Behaviour of FMCG Consumers - Aggarwal, Rashmi (Journal of Research in Marketing (ISSN: 2292-9355), 2013)
This study uses regression analysis to determine the effect of demographic characteristics on information search behaviour of FMCG consumers so as to extract the most influential demographic element influencing the information search behaviour. Further correlation matrix is used to analyse the interdependence of demographic variables. Finally marketing implications are suggested.